2022
DOI: 10.52398/gjsd.2022.v2.i2.pp51-72
|View full text |Cite
|
Sign up to set email alerts
|

Echoes of Our Favourite Childhood Figures

Abstract: Since its founding, Disney has become the symbol of values such as joy, magic, entertainment, and family in our lives through loveable stories, characters, and unique experiences. Disney also has had a significant impact on youth culture with its ability to appeal to universal human experiences through its versatile character portfolio. Disney's recent tendency to reproduce their earlier success in modern adaptations (e.g., The Little Mermaid and Snow White coming in 2023) is the focus of this paper. It aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…The sample composition was presumably influenced by the requirements of the IAT (Qualtrics) and the online data collection method, having a predominantly young, female population with a university degree. It is worth noting that this finding is aligned with recent observations made in Hungary across different domains using IAT (Fuduric et al, 2022;Griszbacher et al, 2022a;2022b). Nonetheless, the effort can be considered as successful to reach a group of young travellers (Travel impact AVG X =4.24, measured on a 1-5 Likert scale), whose daily habits (i.e., travelling) were heavily influenced by the pandemic.…”
Section: Analysis and Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The sample composition was presumably influenced by the requirements of the IAT (Qualtrics) and the online data collection method, having a predominantly young, female population with a university degree. It is worth noting that this finding is aligned with recent observations made in Hungary across different domains using IAT (Fuduric et al, 2022;Griszbacher et al, 2022a;2022b). Nonetheless, the effort can be considered as successful to reach a group of young travellers (Travel impact AVG X =4.24, measured on a 1-5 Likert scale), whose daily habits (i.e., travelling) were heavily influenced by the pandemic.…”
Section: Analysis and Resultssupporting
confidence: 83%
“…The study showcased the applicability of IAT as a non-invasive unconscious technique in addressing present-day tourism challenges, such as COVID-19 and leaning towards nature-based experiences (RQ1-2-3). Consistent with prior IAT research, the findings suggest that despite a weak correlation observed in this instance, implicit and explicit measures are closely aligned and congruent (i.e., indicating a natural preference HUN-RO), making this revolutionary combination more effective (reliable) to measure consumer attitudes and preferences (Fuduric et al, 2022;Griszbacher et al, 2022a;2022b). Consequently, these findings can provide a firm foundation for future discussions; however, it is essential to recognize the limitations of the current study.…”
Section: Studies and Articlessupporting
confidence: 80%
See 1 more Smart Citation